Developing algorithms to determine an Asteroid’s physical properties and the success of deflection missions - Nath, Arushi (Acta astronautica, 2024)
The rate of discovery of near-Earth asteroids currently outpaces our ability to analyze them. Knowledge of an asteroid's physical properties is essential to deflect them. I developed free and open-source algorithms and training modules. These tools utilize images from robotic telescopes, open-source data, and high school-level mathematics to determine asteroids' size, rotation period, and strength. I took observations of the Didymos binary asteroid, and my algorithm determined its size to be 850 ± 0.04 m, with a 2.261 ± 0.018 h rotation period and rubble-pile strength. I measured a decrease in the mutual orbital period after impact by NASA's 2022 DART Mission, confirming successful deflection. My findings matched closely with those obtained by NASA and external sources (Daly et al., 2023; Thomas et al., 2023; Talbert, 2022, October 11; Nakanoet al., 2022) [1,2,3,4]. Every young person and citizen scientist can now be a planetary defender. •Rate of discovery of near-earth asteroids outpaces current abilities to analyze them.•Open data can help citizen scientists determine asteroid's physical properties.•Algorithms successfully measured success of DART Mission in deflecting Dimorphos.•Citizen scientist participation can provide valuable inputs for planetary defense considerations.